Ejerskabsstrukturer og kontrolallokering i unoterede danske virksomheder - Morten Bennedsen; Kasper Nielsen (Copenhagen Business School (CBS), Department of Economics, 2001)
– We analyse the relationship between the distribution of ownership and the allocation of control in Danish closely held corporations. First, we investigate why firms have boards. Second, we identify relationships between owners, boardmembers and CEOs in these firms. Third, we show the presence of control dilution in firms with multiple owners. Finally, we discuss some implications for Danish corporate law of our findings.
hdl:10398/7536
Keywords: G30; 330; Allocation of control; Denmark; closely held corporations; boardmembers; Corporate Law; Corporate governance